Occurrence of Multi-Drug Resistant Escherichia Coli and Escherichia Coli O157:H7 in Meat and Swab Samples of Various Contact Surfaces at Abattoir and Butcher Shops in Jimma Town, Southwest District of Ethiopia - Sebsibe MA; Asfaw ET (Infection and Drug Resistance, 2020)
Mengistu Abayneh Sebsibe, Eyob Tekalign Asfaw School of Medical Laboratory Sciences, Mizan-Tepi University, Mizan Teferi, EthiopiaCorrespondence: Mengistu Abayneh Sebsibe Email menge.abay@gmail.comBackground: Raw meat is one of the commonly consumed traditional diets in Ethiopia. However, unhygienic processing and distribution practices are risky for contamination of meat leading to human infection. This study was conducted to assess the presence of multi-drug resistant E. coli with special emphasis on E. coli O157:H7 from meat of cattle and swab samples at abattoir houses and butcher shops in Jimma town, Southwest district of Ethiopia.Methodology: A cross-sectional descriptive study was conducted from April to July, 2018. The isolation and identification processes passed through enrichment of samples with modified tryptone soy broth (mTSB), streaked onto MacConkey agar and Cefixime-tellurite sorbitol MacConkey agar, biochemical testing (indole and TSI), followed by latex agglutination testing.Results: Out of 505 samples, 102 (20.2%) and 27 (5.4%) were positive for E. coli and E. coli O157:H7, respectively. Of these, 55 (19.3%) and 47 (21.4%) of E. coli and 17 (6.0%) and 10 (4.5%) of E. coli O157:H7 were isolated from the abattoir and butcher shop samples, respectively. A significant difference in the occurrences was observed among sample sources. Antimicrobial susceptibility test results showed that, 92.2% to 96.1% of E. coli and 85.5% to 96.3% of E. coli O157:H7 were susceptible to third generation cephalosporin, ciprofloxacin, gentamycin, kanamycin, streptomycin, and chloramphenicol. About 91.2% and 97.1% of E. coli and 88.9% and 92.6% of E. coli 0157:H7 were resistant to ampicillin and erythromycin, respectively. A total of 57 (44.2%) E. coli and E. coli O157:H7 isolates were resistant to three or more classes of antibiotics. All abattoir and butcher shop workers did not have any formal education or training certificates on food safety, and unhygienic practices were also observed.Conclusion: The presence of E. coli and E. coli O157:H7 including multi-drug resistant isolates in raw meat highlights how the current meat processing and distribution practice was unhygienic. Therefore, strategies in the prevention and control of food-borne infections that could be caused by multi-drug resistant strains will depend greatly on hygienic processing and distribution practices of meat.Keywords: multi-drug resistant E. coli and E. coli O157:H7, abattoir and butcher shops, Jimma town